Graphene oxide photonics. (9th April 2019) - Ghofraniha, Neda; Conti, Claudio
Abstract: The successful exfoliation of graphite has initiated new science in many research fields and is employing a huge number of scientists in the world investigating the chemical, structural, mechanical and optoelectrical properties of the atomic-thick sheets of graphene and graphene oxide (GO). Similarly to other carbon-based materials, the graphene family have shown exceptional optical responses and nowadays it is engineered to produce efficient photonic components. In this review, we aim to summarize the main results in nonlinear optical response and fluorescence of GO. Moreover, its laser printing is reviewed as a novel promising lithographic technique.